Time lag model on the concentration and secretion control in male reproductive hormones - Nkuturum, Christiana; Ogan, Fortune Magnus (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2023)
This study explored the time lag model on testosterone secretion control in male reproductive hormones. It revealed a lag in velocity and frequency on the luteinizing hormone-releasing hormone or LHRH (R) thereby leaving a time lag in its position and wavelength. Time delays are potent sources of instability in population growth systems and human beings since they are ubiquitous in ecological systems. Time lag can be explained by the rule that an otherwise stable equilibrium will generally become unstable if a time delay exceeds the dominant time scale of a system. This study considered a negative feedback function of frequency in the form of a travelling wave in the negative x-direction to explain the inhibition of the Luteinizing hormone (L). The study also showcased that the time lag or delay in the secretion of testosterone (T) led to its decay or extinction completely. The system also displayed a stable and significant effect of time lag of testosterone concentration and secretion in male reproductive hormones. The study recommended that clinical routine checkups should be adhered to by men and plans for the treatment should be effective.